To train the protagonist of education - Cervera Vallejos, Mirtha Flor (2020)
Never before has teaching been so closely linked and with such successful interaction between students and teachers as in the times of Covid-19, permitted by the plausible virtual classroom and zoon, a limitation that did not prevent the art of continuing to form the most valuable part of an Alma Mater for university students in general and for nurses in particular.